2016
DOI: 10.1093/brain/aww132
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal famine exposure has sex-specific effects on brain size

Abstract: Early nutritional deprivation might cause irreversible damage to the brain. Prenatal exposure to undernutrition has been shown to be associated with increased central nervous system anomalies at birth and decreased cognitive function in adulthood. Little is known about the potential effect on the brain in older age. We investigated brain size and structure at age 68 years after prenatal famine exposure. T1-weighted structural magnetic resonance images of the brain were made in 118 Dutch famine birth cohort mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 26 publications
2
50
1
2
Order By: Relevance
“…Our results are also in line with prior studies in humans that have observed sex differences in the effects of prenatal exposures on brain development (de Rooij et al, ; Treit et al, ). Evans and Myatt () showed that male fetuses of obese mothers have higher levels of reactive oxidative species compared to female fetuses (Evans & Myatt, ).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are also in line with prior studies in humans that have observed sex differences in the effects of prenatal exposures on brain development (de Rooij et al, ; Treit et al, ). Evans and Myatt () showed that male fetuses of obese mothers have higher levels of reactive oxidative species compared to female fetuses (Evans & Myatt, ).…”
Section: Discussionsupporting
confidence: 93%
“…The translational power of these studies is shown by a parallel MRI study in the Dutch famine birth cohort, in which decreased total brain volume in late adulthood was already shown in those who had been undernourished prenatally (de Rooij et al, 2016). Further research in the Dutch famine birth cohort will investigate whether exposure to fetal undernutrition during early gestation has an effect on individual brain aging in late-life.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, cardiovascular mortality (but not morbidity) was increased among women exposed to famine in early gestation (Van Abeelen et al 2012a, Ekamper et al 2014. However, other effects were more pronounced in men: the overall smaller size of the brain after prenatal famine exposure was only found in men and not women (de Rooij et al 2016). Also a number of mental disorders, including addiction and depression, are more common after prenatal exposure to famine in men (Franzek et al 2008, Stein et al 2009.…”
Section: Sex Differencesmentioning
confidence: 97%
“…Prenatal famine exposure has also been associated with affective psychoses and depression, though not all studies replicated this finding (Stein et al 2009, de Rooij et al 2011. Imaging studies of the brains have shown lasting effects of famine exposure on brain size and structure (Hulshoff Pol et al 2000, de Rooij et al 2016. Men who had been exposed to famine in early gestation had smaller intracortical volumes and total brain volumes than unexposed men.…”
Section: Central Nervous Systemmentioning
confidence: 99%